Jihad Dalam Perspektif Al-Qur'an - Darwo Maryono (ZAD Al-Mufassirin, 2022)
The mission of jihad in islam, which is very noble today, is smeared with a misunderstanding of its concept. This paper explains the meaning of jihad in Islam to correct the understanding of some people who are mistaken in understanding the meaning of jihad according to the perspective of the Qur'ân. This paper uses the thematic interpretation method. Based on the results of the discussion, jihad is the effort of a Muslim who devotes all his abilities in resisting evil and eliminating evil, starting from jihad against evil and ugliness in himself by defeating the persuasion and seduction of demons in himself, then fighting evil in the society in which he lives, to eliminating evil anywhere according to his ability